Correlation between Severity of Coronary Artery Stenosis and Perfusion Defect Assessed by SPECT Myocardial Perfusion Imaging - Zaman, MM; Haque, SS; Siddique, MA; Banerjee, S; Ahmed, CM; Sharma, AK; Rahman, MF; Haque, MH; Joarder, AI; Sultan, AU; et al. (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):608-13 The abstract of this article is available on the PubMed website